In-plane anisotropy in deformation micro-mechanism of commercially pure titanium during monotonic tension and cyclic loading - Atasi Ghosh (Fracture and Structural Integrity)
In the present investigation in-plane anisotropy in tensile and ratcheting behavior of cold rolled and annealed commercially pure titanium plate has been studied. Flat tensile and fatigue test specimen oriented at 0, 45, and 90 degree to the rolling direction from the rolling directiontransverse direction (RDTD) plane of the plate has been machined out. Specimens with loading axis at 0, 45 and 90 degree to RD have been designated as 0T, 45T and 90T for tensile and 0R, 45R and 90R for fatigue. Owing to initial TD split basal texture of as received plate, 0T sample has crystallographic direction aligned with loading axis. It shows lowest yield strength but highest ductility in monotonic tension. Although ultimate tensile strength (UTS) and strain to failure of samples 45T and 90T are similar, the former has significantly lower yield strength than the latter, indicating different strain-hardening behavior due to different slip/twin activity. On the other hand, 0R sample exhibits longer ratcheting life while 90R sample accumulates highest ratcheting strain. This has been attributed to the formation of intersecting multi-variant twins, which increases fatigue crack propagation resistance during cyclic deformation of 0R sample. Viscoplastic self-consistent (VPSC) simulations of one-cycle tension-compression-reload tension indicate alternating activity of pyramidal c+a slip and extension twinning with loading cycle. The detwinning of extension twin during compression cycle induces cross slip activity, which causes rapid accumulation of strain leading to early fatigue failure of 45R and 90R sample.